50 queers who changed the world : a celebration of LGBTQ+ icons - Jones, Dan; Rosenthal, Michele (London : Hardie Grant Books, 2017)
"LGBTQ people are some of the coolest in history - legendary figures such as Freddie Mercury, Virginia Woolf, Laverne Cox, Harvey Milk and Audre Lorde have made an unforgettable impact. Queer subculture has had an enormous influence on style, music, art and literature - the queer community were the first to vogue, throw shade and say YAS to life before it hit the mainstream. From Oscar Wilde, who defended his homosexual relationships in court, to RuPaul acting as an ambassador for drag on network television, queer people have fought to express their identities and make a difference. This book will celebrate the lives, work and unique perspectives of the icons who changed the world."
Keywords: aktivistit; aktivismi; perusoikeudet; seksuaalivähemmistöt; sukupuolivähemmistöt; homoseksuaalisuus; historia; transsukupuolisuus; sukupuoli-identiteetti; homot; lesbot; transihmiset; kulttuurivaikuttajat; henkilöhistoria; henkilökuvat